2013
DOI: 10.1007/s00138-013-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time landing place assessment in man-made environments

Abstract: We propose a novel approach to real-time landing site detection and assessment in unconstrained man-made environments using passive sensors. Because this task must be performed in a few seconds or less, existing methods are often limited to simple local intensity and edge variation cues. By contrast, we show how to efficiently take into account the potential sites' global shape, which is a critical cue in man-made scenes. Our method relies on a new segmentation algorithm and shape regularity measure to look fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…The first is conceived as the fully automatic or autonomous vehicle, capable of completing an entire flight by itself, with input from the occupant only in terms of routing and (in the case of the automatic vehicle) observation and monitoring of the vehicle's systems [10,11]. The second approach, perhaps for earlier versions of a PAV and the subject of this paper, would require the human occupant to control some, or all, of the piloting functions of the vehicle.…”
Section: Autonomous Vs Augmented Flightmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is conceived as the fully automatic or autonomous vehicle, capable of completing an entire flight by itself, with input from the occupant only in terms of routing and (in the case of the automatic vehicle) observation and monitoring of the vehicle's systems [10,11]. The second approach, perhaps for earlier versions of a PAV and the subject of this paper, would require the human occupant to control some, or all, of the piloting functions of the vehicle.…”
Section: Autonomous Vs Augmented Flightmentioning
confidence: 99%
“…This covered control of the aircraft in forward flight. Whilst the characteristics of the individual control axes could be learned quite quickly, all of the TSs found that more time was required to reach the acceptable standard when simultaneous, coordinated multiple control inputs had to be made (skills [11][12][13][14]. As with the single-axis tasks, moving the controls to start the PAV moving in the correct sense was not demanding for the TSs.…”
Section: Training Durationmentioning
confidence: 99%
“…As polygonal outlines should be evaluated not only according to their geometry but also to the color and texture of the area they enclose, we take our line fragments to be straight segments extracted using a hough-style algorithm from the boundaries of Maximally Stable Extremal Regions (MSERs) [30]. We find MSERs using a combined edge and intensity image whose edge scores are computed with the method of [1] as described in [42]. This results in a better over-segmentation of the image that more faithfully respects its underlying contours.…”
Section: Graph Constructionmentioning
confidence: 99%
“…When they are not, an ad hoc heuristic designed to achieve convergence, which essentially smooths steps by averaging between the next and current iterate, has been used over the years. This heuristic is mentioned explicitly in some works [28,7,13], or used implicitly in optimization schemes [12,30] by introducing an additional damping parameter.…”
Section: Introductionmentioning
confidence: 99%